Re-membering Publicness - Cooper , Jayson (Journal of Public Pedagogies, 2022)
In this short multimodal text I scratch away and make visible the colonial and consumerist ideals of ownership that are etched over Southern landscapes; shaping the cultural commons and common worlds (Bowers, 2009; Hodgins, 2019). Colonial structures advance the enclosure and erasure of public spaces via a rhetoric of turning the earth to your advantage (Cooper, 2015). This views the South—Indigenous minds, bodies, and territories (Tuck & Yang, 2014) — as a table rasa waiting to be developed. The colonial project’s terraforming practices of places has distorted natural systems and patterns that manifest a public pedagogy of forgetting. This is more complex than environmental education and related discourses as it seeps across the political, social, environmental, ethical and the identities of contemporary Australian publicness (Fletcher et al., 2020). Refusing this narrative this text makes visible some wounds inflicted by the ongoing advancement of colonisation. Storying Country (Phillips & Bunda, 2018) through multimodality re-members and re-turns (Barad, 2014) the complexities of Place; to decolonise settler notions (Hamm, 2017). Decolonising publics is complex work. For sustainable futures all narratives of Place are important. This ethic calls for the refusal, resistance, and rejection of forgetting in order to come alongside Indigenous and Southern ways of knowing, being and doing (Martin, 2006). Staying with the always-already constitutions that generate public pedagogy learning ecologies relations with Country can be made visible to create new discursive practices through the arts. Doing this with Place allows for discourse on decolonising the public sphere. In this text I compose a multimodal text (Arnott & Yelland, 2020) that stories the palimpsestsous nature of being in relation-with Place through a pedagogy of intra-action (Cooper & Sandlin, 2020). Staying with the scarification and development of Joan’s/Jones creek; a seasonal creek in Wurundjeri Country (in the western suburbs of Naarm (Melbourne), Australia).